Dimensies van leierskapsbeoefening deur verpleegdiensbestuurders - A. Nel; M. Muller; M. Poggenpoel (AOSIS, 1996)
Leadership development is an important component of the nursing service manager's personal and professional development. Competent leadership is required to lead the nursing service in the right direction within the context of dynamic political and social changes. Various internal and external environmental variables have a significant influence on leadership behaviour and practice. The purpose with this study is to explore and describe the characteristics or dimensions of leadership excellence by the nursing service manager. An exporatory and descriptive research design was followed and data collection was done by means of focus group interviews. The results do not show a significant difference between the knowledge already generated by research, or described in the literature, but is utilised as the basis of leadership development of nursing service managers. A leadership development programme for nursing service managers, based on the results of this study, is recommended.